2021
DOI: 10.1055/a-1376-0970
|View full text |Cite
|
Sign up to set email alerts
|

A Practical, One-Clinic Visit Protocol for Pharmacokinetic Profile Generation with the ADVATE myPKFiT Dosing Tool in Severe Hemophilia A Subjects

Abstract: Standard pharmacokinetic (PK) assessments are demanding for persons with hemophilia A, requiring a 72hr washout and 5-11 timed blood samples. A no-washout, single-clinic visit, sparse sampling population PK (PPK) protocol is an attractive alternative. Here, we compared PK parameters obtained with a traditional washout, 6-sampling time point PPK protocol with a no-washout, single-clinic visit, reverse 2-sampling time point PPK protocol in persons with severe hemophilia A (SHA) receiving ADVATE®. 39 inhibitor-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
(59 reference statements)
2
10
0
1
Order By: Relevance
“…But there are still about 50% of patients with unknown causes, unable to target the cause of treatment and plaguing patients. Studies have shown that screening for thrombotic genes is effective in preventing unexplained recurrent abortions [ 9 ]. Coagulation factor vWF is a serine protease synthesized by the liver and plays an important role in fibrinolysis and coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…But there are still about 50% of patients with unknown causes, unable to target the cause of treatment and plaguing patients. Studies have shown that screening for thrombotic genes is effective in preventing unexplained recurrent abortions [ 9 ]. Coagulation factor vWF is a serine protease synthesized by the liver and plays an important role in fibrinolysis and coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Furthermore, the study of Blanchette et al compared a 6-sample design to a 2-sample design in a PK study of Advate with 39 patients with hemophilia A, and concluded that the 2-sample design showed su cient accuracy to be used in routine clinical care. [29] This conclusion was based on an substantial and almost perfect interclass correlation for clearance (0.73) and t1/2 (0.84) between the PK parameters in the 6-and 2sample design. Though, it should be noted that the PK parameters calculated with a 6-sample design are not the exact (true) individual PK parameters, making the agreement of the 2-sample design with true individual PK parameters smaller.…”
Section: Discussionmentioning
confidence: 96%
“…Personalized LSA can be used to ask for a patient to come back to clinic a few days later, however this may not be optimal as it will add one extra clinic visit. To prevent extra visits, it is possible to perform a two‐sample protocol: during one unique clinic visit, one sample is obtained at trough—shortly before infusion of FVIII; and one sample is obtained at peak—shortly after the same infusion of FVIII 10,13 . Personalized LSA can leverage a previous PK assessment and derive the sampling time of trough for such two‐sample protocols.…”
Section: Discussionmentioning
confidence: 99%